The incidence of pseudoprogressive disease associated with programmed cell death 1/programmed cell death ligand 1 inhibitors: A meta-analysis. Issue 28 (16th July 2021) - Zhang, Jingyi; Tan, Kexin; Jiang, Xuejiao; Zheng, Shuyue; Li, Jia; Xue, Chongxiang; Zhang, Xu; Cui, Huijuan
Abstract: Background: The method to evaluate the efficacy of programmed cell death 1 (PD-1)/programmed cell death ligand 1 (PD-L1) inhibitors has become a big concern for researchers with its widely application. Pseudoprogressive disease (PPD) makes this process more difficult, which means that the tumor progressed at the initial evaluation, but re-evaluation after continued treatment suggested that the treatment was effective. However, PPD has not attracted enough attention of clinical doctors. This article is to systematically evaluate the incidence of PPD associated with PD-1/PD-L1 inhibitors with meta-analysis, to provide guidance for the recognition and management of PPD. Methods: The databases of PubMed, EMBase, Cochrane Library were retrieved from the earliest collection date of the databases until Dec 5, 2019. The search terms of "pseudoprogressive disease, anti-PD-1, anti-PD-L1, PD-1/PD-L1 inhibitor, etc" were used for logistic combination search. Published studies on PPD caused by PD-1/PD-L1 inhibitors were included. Meta-analysis was performed with Stata 15.1. Subgroup analysis was performed according to the study population, tumor type, and evaluation criteria for efficacy. Results: Seven researches, including 1458 patients were taken into the study. Meta-analysis showed that the overall incidence of PPD was 3.70% (95% confidence interval [CI]: 2.70%, 4.90%). Subgroup analysis showed that the incidence of PPD was 3.30% (95% CI: 1.90%, 5.90%) in non-small cell lung cancer patients and 5.10% (95% CI: 2.30%, 11.6%) in melanoma patients. There was no statistically significant difference between East and West populations and among various efficacy evaluation criteria. Conclusion: The incidence of PPD related to PD-1/PD-L1 inhibitors is not high, but the evaluation criteria has not yet been unified. Close monitoring, careful identification and proper application should be carried out in the clinic, and full management of the treatment with PD-1/PD-L1 inhibitors should be well done.